Conservation strategy of a nature reserve in Mediterranean ecosystems: the effects of protection from grazing on biodiversity - Verdú, J. R.; Crespo, M. B.; Galante, Eduardo (Biodiversity and Conservation, 2000)
Protection of natural areas has caused the elimination of traditional grazing activity on many occasions. As a result, in Mediterranean ecosystems a loss of biodiversity is usually related to a decrease of grassland and grassland–bush mosaic areas. In order to establish relationships between land use and the relative importance of each type of habitat in terms of species richness and endemicity, the Font Roja Natural Park in Alicante Province (SE Iberian Peninsula) was studied. Four sites were selected representing the four different existing habitats: a wooded area (holm-oak forest), a dense shrubland, a dense grassland, and a grassland–shrubland mosaic area. In each site, the species composition of vegetation and dung beetle fauna were analysed. The results showed that the highest diversity and endemicity, for plants and beetles, were concentrated in the dense grasslands and the grassland–shrubland mosaic. Thus, controlled grazing activity of sheep and goats which maintained a diverse variegated landscape would favour the historical sustenance of the biodiversity of Mediterranean ecosystems, as that would allow a remarkable diversity of habitats with higher conservation levels of existing species richness and endemicity. Therefore, we propose a reintroduction of traditional grazing of sheep and goats throughout ecological, cultural and economical measures, which would include guidelines and regulations, set out to boost an integrated rural policy.
Keywords: dung beetles; endemicity; impact; management; vascular plants

Conservation strategy of a nature reserve in Mediterranean ecosystems: the effects of protection from grazing on biodiversity - Verdú, J R; Crespo, M B; Galante, Eduardo (Biodiversity and Conservation, 2000)
Protection of natural areas has caused the elimination of traditional grazing activity on many occasions. As a result, in Mediterranean ecosystems a loss of biodiversity is usually related to a decrease of grassland and grassland–bush mosaic areas. In order to establish relationships between land use and the relative importance of each type of habitat in terms of species richness and endemicity, the Font Roja Natural Park in Alicante Province (SE Iberian Peninsula) was studied. Four sites were selected representing the four different existing habitats: a wooded area (holm-oak forest), a dense shrubland, a dense grassland, and a grassland–shrubland mosaic area. In each site, the species composition of vegetation and dung beetle fauna were analysed. The results showed that the highest diversity and endemicity, for plants and beetles, were concentrated in the dense grasslands and the grassland–shrubland mosaic. Thus, controlled grazing activity of sheep and goats which maintained a diverse variegated landscape would favour the historical sustenance of the biodiversity of Mediterranean ecosystems, as that would allow a remarkable diversity of habitats with higher conservation levels of existing species richness and endemicity. Therefore, we propose a reintroduction of traditional grazing of sheep and goats throughout ecological, cultural and economical measures, which would include guidelines and regulations, set out to boost an integrated rural policy.
Keywords: dung beetles; endemicity; impact; management; vascular plants

Dung Beetles (Coleoptera: Scarabaeidae, Geotrupidae) Attracted to Fresh Cattle Dung in Wooded and Open Pasture - Galante, Eduardo; MENA, JAVIER; LUMBRERAS, CARLOS (Environmental Entomology, 1995)
The biomass of dung beetles attracted to fresh cattle dung was studied in a Mediterranean holm oak pasture ecosystem with a continental Mediterranean climate (supramediterranean level). Results indicated a nonuniform biomass distribution of dung beetles throughout the year. Major peaks of species activity and biomass concentration of dung beetles occurred in open areas of the pasture in the spring followed by minor peaks in the fall. Beetle biomass in the open pasture was greater than that in the wooded pasture. The species of dung beetles comprising the greatest amount of biomass and the most important species available to destroy cattle dung pats in Mediterranean ecosystemswith a continental climate were Bubas bubalus Olivier, Onthophagus opacicollis d'Orbigny, Copris hispanus (L.), Copris lunaris (L.), and Onthophagus vacca (L.).
Keywords: biomass; dung beetles; Holm oak; Mediterranean ecosystem; pastureland

Dung Beetles (Coleoptera: Scarabaeidae, Geotrupidae) Attracted to Fresh Cattle Dung in Wooded and Open Pasture - Galante, Eduardo; MENA, JAVIER; LUMBRERAS, CARLOS (Environmental Entomology, 1995)
The biomass of dung beetles attracted to fresh cattle dung was studied in a Mediterranean holm oak pasture ecosystem with a continental Mediterranean climate (supramediterranean level). Results indicated a nonuniform biomass distribution of dung beetles throughout the year. Major peaks of species activity and biomass concentration of dung beetles occurred in open areas of the pasture in the spring followed by minor peaks in the fall. Beetle biomass in the open pasture was greater than that in the wooded pasture. The species of dung beetles comprising the greatest amount of biomass and the most important species available to destroy cattle dung pats in Mediterranean ecosystemswith a continental climate were Bubas bubalus Olivier, Onthophagus opacicollis d'Orbigny, Copris hispanus (L.), Copris lunaris (L.), and Onthophagus vacca (L.).
Keywords: biomass; dung beetles; Holm oak; Mediterranean ecosystem; pastureland

Comparison of Spatial Distribution Patterns of Dung-Feeding Scarabs (Coleoptera: Scarabaeidae, Geotrupidae) in Wooded and Open Pastureland in the Mediterranean “Dehesa” Area of the Iberian Peninsula - GALANTE, E; GARCIA-ROMAN, M; BARRERA, I; GALINDO, P (Environmental Entomology, 1991)
The seasonal and spatial distributions of dung-feeding scarabs in an open pastureland and in wooded (holm oak) pastureland in a typical Mediterranean area of the western part of the Iberian Peninsula (Salamanca) were compared. Six pitfall traps baited with bovine dung were placed in each habitat according to a model by J. P. Lumaret. Only beetles in the families Scarabaeidae and Geotrupidae were studied because they are the most important agents in the elimination of cattle dung from the soil surface. Weekly trapping for 1 yr produced 6,909 specimens. Of the 18 species found, the largest beetles and biomass were concentrated mainly in the wooded habitat, especially in the summer. This constitutes a problem for dung removal because large amounts of dung remain in open pasturelands, possibly resulting in the impoverishment of such areas.
Keywords: dung beetles; Geotrupidae; Insecta; Scarabaeidae